Exploring physiological traits for measuring response to competition in durum wheat. (2nd January 2020) - Henry, L; Morel, Jb; Buendia, L
ABSTRACT: Studies of the effect of plant density have been conducted in numerous crops. However, most of them focused on yield to evaluate the impact of plant competition. In this study, we determined the best functional trait to detect early competition responses affecting plant growth. To do so, we designed experiments with increasing sowing density using two different durum wheat genotypes. Height from crown to the last liguled leaf and dry weight decreased with increasing sowing density showing that these traits are suitable to measure early competition responses. However, specific leaf area, a common-measured trait to study competition was not affected by sowing density at early stages. We conclude that plant density is a modifier of plant growth at the early stages of plant growth and that dry weight as well as height from crown to the last liguled leaf are the best functional traits to be measured.